2003
DOI: 10.1002/med.10059
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in selective opioid receptor agonists and antagonists

Abstract: Opioid analgesics provide outstanding benefits for relief of severe pain. The mechanisms of the analgesia accompanied with some side effects have been investigated by many scientists to shed light on the complex biological processes at the molecular level. New opioid drugs and therapies with more desirable properties can be developed on the bases of accurate insight of the opioid ligand-receptor interaction and clear knowledge of the pharmacological behavior of opioid receptors and the associated proteins. Tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 171 publications
(147 reference statements)
2
112
0
3
Order By: Relevance
“…Naloxone and naltrexone, although pure mu antagonists, are only moderately selective for the mu opioid receptor. [12] In 1981, Portoghese described the first selective mu opioid antagonist, b-funaltrexamine (b-FNA) 11 (Figure 3), a site-directed alkylating agent that binds covalently to mu opioid receptors. [13] b-FNA, an analogue of b-naltrexamine 10, initially binds to all three opioid receptors, but because of very subtle structural differences within the receptor subtypes this compound alkylates, in vitro, only mu opioid receptors.…”
Section: Morphinansmentioning
confidence: 99%
“…Naloxone and naltrexone, although pure mu antagonists, are only moderately selective for the mu opioid receptor. [12] In 1981, Portoghese described the first selective mu opioid antagonist, b-funaltrexamine (b-FNA) 11 (Figure 3), a site-directed alkylating agent that binds covalently to mu opioid receptors. [13] b-FNA, an analogue of b-naltrexamine 10, initially binds to all three opioid receptors, but because of very subtle structural differences within the receptor subtypes this compound alkylates, in vitro, only mu opioid receptors.…”
Section: Morphinansmentioning
confidence: 99%
“…Indeed, the ionic bond between the protonated amine and a conserved Asp of the receptor is considered the driving force of the ligand-receptor interaction for all kinds of endogenous opioid peptides [3,5] as well as for exogenous agonists, [6] such as morphine (1) and fentanyls. [7] In most cases, the removal or derivatization of this group resulted in inactive derivatives or antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we focused on incorporating an indole or thiazole fragment as the heterocyclic function. Although indole and other heterocycles have been successfully introduced [2,3] at the right side (ring C) of the morphine molecule as the "address" component in the "messageaddress" concept [13,14] resulting in many compounds with interesting pharmacological activities at various opioid receptors, including the well-established d receptor antagonist naltrindole (1) [15] and the k-selective agonist 6'-GNTI (2), [16] fusing such heterocyclic functions to the 14-hydroxymorphinan skeleton has not been well explored. In 1999 and 2007, Coop, Rice, and co-workers [17][18][19] reported a series of compounds by breaking the 4,5-furan ring of naltrindole (1), and found that 14-hydroxyindolomorphinans 3 and 4 with a 4-hydroxy or methoxy group retained reasonable affinity and selectivity for the d receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most of the opioid receptor ligands currently available originate mainly from alkaloid, morphine, codeine, or thebaine. [2][3][4][5][6] As part of our long-term objective to develop compounds possessing mixed activities at k and m opioid receptors as potential therapeutics for analgesics and treatment for drug abuse, [7][8][9][10][11][12] we recently became interested in the development of 14-hydroxymorphinan analogues characterized by the absence of the 4,5-furan oxygen bridge of morphine and by the incorporation of a heterocyclic functionality at the right side (ring C) of these molecules. In particular, we focused on incorporating an indole or thiazole fragment as the heterocyclic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation